A secure and effective access control scheme for distributed wireless sensor networks. (1st January 2015) - Chatterjee, Santanu; Das, Ashok Kumar; Sing, Jamuna Kanta
The deployment of new nodes is often required in order to extend the lifetime of the sensor network because sensor network may be lost due to power exhaustion problem or deployment of malicious nodes by an attacker. To protect malicious nodes from joining the network, designing of access control schemes becomes a major challenging problem. In this paper, we first review the Huang-Liu's access control scheme. Though their scheme is energy efficient requiring low computational and communication overheads, but we show that their scheme is insecure against node replication attacks as well as it does not provide the mutual authentication between the base station (BS) and sensor nodes. We aim to propose a new efficient and secure access control scheme in order to remedy such security weaknesses found in Huang-Liu's scheme. Our proposed scheme makes use of only the one-way hash function and bitwise XOR operations for providing the authentication and key establishment. Our scheme also requires significantly less communication and computational costs as compared to other related schemes. We show through both informal and formal security analysis that our scheme has the ability to tolerate various known attacks. We further simulate our scheme for formal security verification using the widely accepted Automated Validation of Internet Security Protocols and Applications (AVISPA) tool and we show that our scheme is secure against passive as well as active attacks.